Analisis Desain dan Fabrikasi Fondasi Tiang Tunggal pada Struktur Jacket Lepas Pantai - Sahwan Ramadhan (Riset Sains dan Teknologi Kelautan, 2026)
The increasing demand for cost-efficient offshore structures has led to the development of alternative foundation systems, one of which is the single pile foundation. This study presents a comprehensive analysis of the design and fabrication aspects of single pile foundations applied to offshore jacket structures. The research focuses on load transfer mechanisms, soil–pile interaction, structural integrity, and fabrication challenges. A combination of analytical methods and literature review is employed to evaluate the feasibility and performance of the system. The results indicate that single pile foundations can provide an efficient and reliable solution under specific soil and loading conditions, provided that detailed geotechnical analysis and strict fabrication quality control are implemented (1).